Error bounds for general mixed quasivariational inequalities - Muhammad Aslam Noor; Khalida Inayat Noor (International Journal of Mathematics and Mathematical Sciences)
It is well known that mixed quasivariational inequalities are equivalent to the implicit fixed-point problems. We use this alternative equivalent formulation to suggest and consider some merit functions for general mixed quasivariational inequalities. We use these merit functions to obtain error bounds for the solution under some mild conditions. Some special cases are also discussed.